(untitled) (SAARC Journal of Tuberculosis, Lung Diseases and HIV/AIDS, 2010)
Aims: To study single dose pharmacokinetics of lamivudine (3TC) in healthy subjects. Methods: Twelve healthy subjects were administered 3TC (150 mg) followed by timed blood and urine collections up to 24 hours. Pharmacokinetic variables and percent dose of 3TC in urine were calculated. Results: Plasma exposure and percent dose of 3TC in urine were highly correlated (p < 0.001; r = 0.96). 3TC concentration at 24 hours was undetectable in all study subjects. Conclusions: Timed urine measurements could be used to study bioavailabilty of 3TC. Plasma 3TC measurements could be used to monitor adherence among HIV-infected patients on antiretroviral treatment. Key words: lamivudine; plasma; urine; compliance to treatment DOI: 10.3126/saarctb.v5i2.3069 SAARC J. Tuber. Lung Dis. HIV/AIDS 2008 Vol.5(2) 6-9